Juvenile Court Statistics, 1982: (United States) ([Verlag nicht ermittelbar], 1985)
These data describe the volume of juvenile cases disposed of by courts in the fifty states, the District of Columbia and the territories of the Virgin Islands and Puerto Rico during calendar year 1982. The data contain all available summary information on children's cases disposed of in courts having jurisdiction over juvenile matters, delinquency status, and dependency or neglect.